Pendugaan Analisis Kemanfaatan Tumpangsari Kacang Nasi (Vigna angularis L.) dan Jagung (Zea mays L.) dalam Sistem Olah Lubang diperkaya Biochar dan Kompos - Andrinaris Bait Lake; Syprianus Ceunfin (Fakultas Pertanian, Universitas Timor, 2019)
The Salome intercropping is planting two or more crops at the same time in the same planting hole. The utilization analysis of the intercropping of red mung bean (V. angularis L.) with maize (Z. Mays L.) on biochar and compost-enriched hole tillage method was performed at the Universitas Timor Faculty of Agriculture demo-plot in May 2018. The design of the salome intercropping analysis used a two-factor randomized network design (RBD). The first factor is that the biochar type consists of 3 levels, i.e. biochar rice husk (B1), sawdust biochar (B2), biochar siam weed (B3). The second element is compost (K), which consists of two stages, respectively compost-free (K0), and compost-free (K0) (K1). The variance results (ANOVA) showed that there was no interaction between the treatment factors, but there were interactions between the maize and the red mung bean in the aggressiveness parameter (A). Compared with other treatments, the Land Equivalent Ratio (LER) and Area Time Equivalent Ratio (ATER) parameters have the highest values (10,34 and 6,40) for non-biochar compost combination treatment (B0K1).